Family Ownership and Leverage of Family-Owned Business in Indonesia: The Role of Family Control as Mediation - Nurul Husna; Abel Tasman (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2024)
This research investigates the direct and indirect effects of family ownership on leverage, with family control acting as a mediating variable in Indonesian family-owned businesses. The primary dataset is sourced from the annual financial reports of family-owned firms listed on the Indonesia Stock Exchange (IDX). The sample consists of 73 family-controlled publicly listed companies, selected through purposive sampling based on specific selection criteria. A quantitative approach is adopted in this study, employing panel data regression analysis using E-Views 13 software. Family ownership serves as the independent variable, leverage as the dependent variable, while family control is introduced as the mediating variable; several control variables, such as asset tangibility, firm size, profitability, net trade credit, financial expenses, and retained earnings, are also considered. The analysis reveals that family ownership does not have a statistically significant direct effect on leverage. Nevertheless, when family control is incorporated as a mediator, family ownership exhibits a significant negative influence on leverage. The Sobel test further confirms that family control fully mediates the relationship between family ownership and leverage.